Social Reality Construction of Muhammadiyah Citizens in Respect of LAZISMU during the Covid-19 Pandemic - Radhiyatul Fithri; Baidarus Baidarus (Universitas Muhammadiyah Magelang, 2021)
For the Indonesian people, LAZISMU, as an Islamic philanthropic institution, shapes the cultural character of zakat, infaq, and alms. Furthermore, following the outbreak of the covid-19 pandemic, the Muhammadiyah encouraged LAZISMU with raising funds for the program under the slogan